Physiological Studies of a Synthetic Gibberellin-Like Bioregulator: II. Effect of Site of Application on Biological Activity - Suttle, Jeffrey C. (1987)
The biological activity of the synthetic gibberellin agonist AC-94,377 (1-[3-chlorophthalimido]-cyclohexanecarboxamide) in certain plants is strictly dependent on the site of application. Root application of AC-94,377 at concentrations greater than or equal to 1 micromolar to seedlings of dwarf corn (Zea mays L. var d(5)), dwarf rice (Oryza sativa L. cv Tan-ginbozu), and sunflower (Helianthus annuus L. cv NK265) seedlings resulted in readily measurable gibberellin-like biological activity. Application of up to 10 micrograms of AC-94,377 to the shoots of these same species had no effect. AC-94,377 was metabolized to more polar products in both dwarf corn and sunflower seedlings. After 4 days of continuous root treatment with [(14)C]AC-94,377, greater than 70% of the recovered (14)C was found in the form of unmetabolized AC-94,377. In contrast, only 30 to 40% of the recovered (14)C was unmetabolized 4 days after shoot treatment. Translocation studies demonstrated that the movement of [(14)C]AC-94,377 was limited and occurred almost exclusively in an apoplastic fashion. Four days after leaf treatment, less than 1.5% (corn) or 4% (sunflower) of the recovered radioactivity had moved away from the treated area. It was concluded that the lack of biological activity of AC-94,377 following shoot treatment resulted principally from limited phloem mobility and to a lesser extent from accelerated metabolic breakdown.